Performance and stability improvements in metal halide perovskite with intralayer incorporation of organic additives. Issue 30 (22nd July 2021) - Li, Yanan; Dailey, Matthew; Lohr, Patrick J.; Printz, Adam D.
Abstract : Organic additives can be used to tune the properties of metal halide perovskites to improve their performance and stability for a wide range of applications, including photovoltaics, thin-film transistors, and light-emitting diodes. Abstract : Metal halide perovskites are emerging semiconducting materials with a wide range of applications, including photovoltaics, thin-film transistors, and light-emitting diodes. A key advantage of perovskites over more established semiconductor technologies is solution processability, which reduces processing costs and enables rapid production by roll-to-roll printing. However, metal halide perovskites suffer from poor thermomechanical and chemical stability that must be overcome for successful commercialization of perovskite-based technologies. These instabilities have been shown to stem from defect states present at perovskite interfaces, and particularly grain boundaries, that result in destructive trap states. This review focuses on one successful strategy—organic additive engineering—that has been demonstrated to inhibit the formation of defect sites in perovskite films. This review begins by discussing defects present at grain boundaries— e.g., undercoordinated bonds, vacancies, and antisites—that develop during crystallization, and how these defects lead to reduced device performance via non-radiative recombination and hysteresis, as well as poor chemical and thermal stability. The bulk of this review is dedicated to additive engineering strategies to enhance performance and stability in 3D, quasi-2D, and 2D perovskites. Lewis acid–base interactions between the additives and perovskite constituents are highlighted, with additives ranging from small molecules and solvents to polymers. Special attention is paid to Lewis base additives containing amino and/or carbonyl functional groups, and a short discussion on semiconducting additives for improved charge transport is also included. This review concludes by identifying several areas of further discovery in organic additives for metal halide perovskites.